Upaya Meningkatkan Hasil Belajar Siswa Pada Materi Menerapkan Perwarnaan Mikroba Melalui Model Pembelajaran Dengan Pendekatan Contextual Teaching And Learning (CTL) Siswa Kelas XI APL - 1 SMKN 1 Cerme Gresik Tahun Pelajaran 2019/2020 - Sukartono, Eka Martina Muawanah, Ida Kurniati, Bekanadi, Ari Kurniati, M. Hekmat (Jurnal Ilmiah Jendela Pendidikan, 2021)
Learning model is selected with a contectual approach (Contextual Teaching And Learning Learning (CTL) in an effort to improve student learning outcomes in the basiccompetencies of Applying Mikrobial Coloring, for this PTK activity, class XI APL -1 was selected, because the researcher was a teacher who taught at class XI APL-1 SMKN 1 Cerme Gresik, The results showed that out of 32 student, there were many students who were less active or indifferent in participating in the teaching and learning process, this can be due to the lack of prerequistes for student to follow the lessons on Applying Mocrobial Coloring material co that this material is considered difficult by some student. Then studfents must be motivated to be more enthusiatic in teaching and learning that is , among orthers, given the questions related to material presented, if the student’s answer is correct, the teacher gives reinforcement or praise so that the student feel happy, The teacher must also tell that the benefits of mastering the material of Applying Microbial Coloring are very important because they can be used to solve problems in everyday life related to Applying Microbial Coloring By looking at the results of student achievement, it turns out that out of 32 student there are 21 students (64%) who can be categorizet as incomplete learning, namely getting a value of < 75, while students who complete learning 12 students (36%) with an average of 67,8 and absorption of the subject matter 67,8%